2019
DOI: 10.1159/000499665
|View full text |Cite
|
Sign up to set email alerts
|

Stent Retriever Thrombectomy Potentially Increases the Recanalization Rate, Improves Clinical Outcome, and Decreases Mortality in Acute Basilar Occlusion: A Systematic Review and Meta-Analysis

Abstract: Background: Acute basilar artery occlusion (BAO) is a devastating condition if untreated. The optimal treatment strategy, however, is unknown. Historically, interventional approaches have been favored over intravenous thrombolysis (IVT), although this is not supported by good evidence. The aim of this systematic review and meta-analysis was to summarize and compare the results for treatment modalities of BAO, namely, IVT and interventional stent retriever thrombectomy (SRT). Methods: Studies on IVT and SRT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…Importantly, they are associated with high mortality and morbidity rates without treatment [1][2][3][4]. As these rates can be reduced dramatically by mechanical thrombectomy (MT), MT is now standard care in most stroke centers [5][6][7][8] despite a lack of evidence by large randomized trials. Outcome rates seem to be comparable to those of large vessel occlusions of the anterior circulation [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, they are associated with high mortality and morbidity rates without treatment [1][2][3][4]. As these rates can be reduced dramatically by mechanical thrombectomy (MT), MT is now standard care in most stroke centers [5][6][7][8] despite a lack of evidence by large randomized trials. Outcome rates seem to be comparable to those of large vessel occlusions of the anterior circulation [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, fewer studies have demonstrated their safety and efficacy in BA strokes. Shu et al [9] proposed that mechanical thrombectomy has a greater efficacy than intravenous thrombolysis. In a review including 672 patients, they reported a higher recanalisation rate in patients treated with stent retriever thrombectomy (88%) than those treated with intravenous thrombolysis (60%) and a lower mortality rate: 26 and 41%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings war diese Untersuchung eine Beobachtungsstudie, und für die intraarterielle Therapiegruppe standen noch keine modernen Behandlungsmethoden zur Verfügung. Die Daten einer zuletzt publizierten Metaanalyse deuten auf eine mögliche Überlegenheit moderner Thrombektomieverfahren gegenüber tPA hin [41].…”
Section: Basilarisverschlussunclassified